The relationship between anxiety sensitivity and clinical outcomes in cardiac rehabilitation: A scoping review - Ebuka Osuji; Peter L. Prior; Neville Suskin; Jefferson C. Frisbee; Stephanie J. Frisbee (Elsevier, 2022)
Background: Despite well-established efficacy for patients with a cardiovascular diagnosis or event, exercise-based cardiac rehabilitation program participation and completion has remained alarmingly low due to both system-level barriers and patient-level factors. Patient mental health, particularly depression, is now recognized as significantly associated with reduced enrollment, participation, attendance, and completion of a cardiac rehabilitation program. More recently, anxiety sensitivity has emerged as an independent construct, related to but distinct from both depression and anxiety. Anxiety sensitivity has been reported to be adversely associated with participation in exercise and, thus, may be important for patients in cardiac rehabilitation. Accordingly, the objective of this study was to conduct a scoping review to summarize the evidence for associations between anxiety sensitivity and cardiovascular disease risk factors, exercise, and clinical outcomes in cardiac rehabilitation. Methods: A formal scoping review, following PRISMA-ScR guidelines, was undertaken. Searches of MEDLINE, Web of Science, CINAHL, PSYCINFO, and Scopus databases were conducted, supplemented by hand searches; studies published through December of 2020 were included. The initial screening was based on titles and abstracts and the second stage of screening was based on full text examination. Results: The final search results included 28 studies. Studies reported statistically significant associations between anxiety sensitivity and exercise, cardiovascular disease, and participation in cardiac rehabilitation. Many studies, however, were conducted in non-clinical, community-based populations; there were few studies conducted in cardiovascular disease and cardiac rehabilitation clinical patient populations. Additionally, significant gaps remain in our understanding of the sex-based differences in the complex relationships between anxiety sensitivity, exercise and cardiac rehabilitation. Conclusion: More research is needed to understand specific associations between anxiety sensitivity and clinical outcomes among clinical cardiovascular disease patients and participants in cardiac rehabilitation programs. Treatment of anxiety sensitivity to optimize clinical outcomes in cardiac rehabilitation programs should be investigated in future studies.